PENGEMBANGAN PROTOTIPE SISTEM PENCATATAN DAN PELAPORAN KEMATIAN IBU DAN PERINATAL PADA DINAS KESEHATAN KABUPATEN CILACAP - , APDENI TRISUKESIH, dr. Ova Emilia, Sp.OG(K), M.Med.Ed, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background Maternal mortality is an important measure of the health of the nation and society. The maternal mortality rate in Cilacap regency in 2010 maternal mortality rate by 33 per 28 799 live births. A decline in the maternal mortality rate in 2011 was 28 per 29 481 live births. But back in 2012 there was an increase of 34 per 30 564 live births. One of the policy recommendations for reducing maternal mortality is the development of maternal and child health data. Research purposes To assess pengembangkan prototype system for recording and reporting of maternal and perinatal mortality and can be used for routine reporting as well as the source of data and information in support of decisions for maternal and child health programs. Expected to contribute to the reduction of maternal mortality and perinatal. Methodology This study uses qualitative action research approach to explore the process of recording and reporting system development and perinatal maternal mortality. The selection method considering that the development of a prototype system of recording and reporting of maternal and perinatal mortality is expected that the collaboration between researchers with clients (potential users) so that the results obtained in accordance with the needs of the prospective user. Results The prototype is generated through the four stages of data shown include maternal identity, pregnancy test results while the report is generated in the form of pregnant women and the risk of death reports. Regular prenatal care can detect early risk factors and addressed as soon as possible. Incidence of maternal deaths are reported as soon as possible with this prototype in addition to reporting is also used for the analysis of the incidence of maternal mortality by looking at antenatal history. Conclusion Recording and reporting of maternal and perinatal mortality can be facilitated with technology-based prototype.